FREEZING CHARACTERISTICS OF TROPICAL FISHES - SHENOY, A VASANTH; PILLA!, V K (Fishery Technology, 2025)
The influence of different prefreezing ice storage periods on thebiochemical and organoleptic qualities of Indian oil sardines (Sardi.nella !ongiceps) in the individual quick frozen (IQF) and block frozen(BF) forms and frozen storage at temperatures of-12°C and-23°Cwas studied. The shelf-Hfe of the sardines varied between 24 and2 weeks for samples iced for 0 to 5 days prior to freezing. Thedeterioration in quality was accompanied by considerable increasein the peroxide value (PV) and free fatty acid (FFA) content anddecrease in saJt extractability of the proteins. These changes weremore rapid at-12°C than at-23°C. BF sardines appeared to bebetter than IQF samples with respect to the biochemical changesalthough the differences in overall organoleptic quality were notsignificant.